2022
DOI: 10.1039/d1nr07927a
|View full text |Cite
|
Sign up to set email alerts
|

HKUST-1 nano metal–organic frameworks combined with ZnGa2O4:Cr3+ near-infrared persistent luminescence nanoparticles for in vivo imaging and tumor chemodynamic and photothermal synergic therapy

Abstract: The multifunctional theranostic nanoplatform based on the combination of persistent luminescent nanoparticles (PLNPs) and metal-organic frameworks (MOFs) has both vivo imaging function and tumor therapeutic drug-loading functions, providing a new...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Using these activatable nanomedicines, the therapeutic efficacy can be greatly improved and the adverse effects of some immune drugs (such as immune checkpoint blockers, cytokines, and adjuvants) have been obviously reduced. Therefore, tumor microenvironment-responsive nanomedicines have shown great prospects for the precise delivery of immune drugs into targeting tumor sites and activation of powerful antitumor immunity in a controllable way …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these activatable nanomedicines, the therapeutic efficacy can be greatly improved and the adverse effects of some immune drugs (such as immune checkpoint blockers, cytokines, and adjuvants) have been obviously reduced. Therefore, tumor microenvironment-responsive nanomedicines have shown great prospects for the precise delivery of immune drugs into targeting tumor sites and activation of powerful antitumor immunity in a controllable way …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tumor microenvironment-responsive nanomedicines have shown great prospects for the precise delivery of immune drugs into targeting tumor sites and activation of powerful antitumor immunity in a controllable way. 20 Due to the tumor-suppression effect, the therapeutic efficacy of sole therapeutic modality is often limited. Nanomedicines can be utilized to integrate various types of therapeutic modalities (such as photothermal therapy (PTT), 21 chemotherapy, 22 immunotherapy, 23 and radiotherapy 24 ) into one single system to allow more effective antitumor therapy via combinational actions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…125 Also, lately, combining NIR persistent luminescent NPs with HKUST-1 MOFs, a multifunctional core–shell nanostructure was synthesized for FL-free NIR Pearl imaging, chemodynamic therapy and PTT synergistic therapy. 126 Furthermore, the first multifunctional lanthanide-MOF, named JXUST-11, containing Eu 3+ ions and benzothiadiazole linkers (H2BTDB), was prepared by Li's group as a naked-eye fluorescent probe to recognize Ga ( iii ) ions and effective imaging tool for the detection of Al( iii ) and Ga( iii ) ions in biological cells. 127…”
Section: Mof-based Nanoplatforms In Monomodal Imagingmentioning
confidence: 99%
“…125 Also, lately, combining NIR persistent luminescent NPs with HKUST-1 MOFs, a multifunctional core-shell nanostructure was synthesized for FL-free NIR Pearl imaging, chemodynamic therapy and PTT synergistic therapy. 126 Furthermore, the first multifunctional lanthanide-MOF, named JXUST-11, containing Eu 3+ ions and benzothiadiazole linkers (H2BTDB), was prepared by Li's group as a naked-eye fluorescent probe to recognize Ga (III) ions and effective imaging tool for the detection of Al(III) and Ga(III) ions in biological cells. 127 Numerous studies have been reported for the fabrication of luminescent metal-organic frameworks (LMOFs) utilizing of luminescent connector organic ligands or metal ions/clusters (exclusively fluorescent lanthanoid ions), 128,129 followed by their integration with photosensitizers 130 and loading of organic fluorescent dye molecules, upconversion nanoparticles (UCNPs), 131 persistent luminescent nanoparticles (PLNPs), 132 quantum dots (QDs), 133 or carbon nanodots (C-dots) in MOFs through a post-combinatory method 134 for various bioimaging applications.…”
Section: Fluorescence Imaging Nanoplatformsmentioning
confidence: 99%
“…[75][76][77] MOFs, which are built from metal ions and organic linkers, are endowed with enormous pore volume, large surface area, and a variety of interaction sites, favoring the encapsulation of diverse molecules, including various drugs. [78][79][80][81][82][83][84] Recently, we developed a persistent luminescent metal-organic framework with persistent NIR luminescence for tumor site-activated persistent luminescence imaging and drug delivery. 85 Besides, various metal ions and organic ligands can endow luminescence, MR imaging, or CT imaging properties for bioimaging.…”
Section: Introductionmentioning
confidence: 99%